THE STUDY ON SEASONAL DYNAMICS AND DEVELOPMENT OF LARVAL STAGES OF CAUSATIVE AGENTS OF CATTLE HYPODERMATOSIS IN THE CHECHEN REPUBLIC - Sh. V. Vatsaev; V. P. Tolokonnikov (Российский паразитологический журнал)
Objective of research: to study the regional epizootology, species composition and bioecological features of development of causative agents of cattle hypodermatosis and elaboration of struggle measures against it in theChechenRepublic.Materials and methods: Data on extensity and intensity of invasion, species composition of causative agents of cattle hypodermatosis, seasonal dynamics, larval approach to the surface of animal back (gadfly larvae deposited in animals' skin), time of the larval-pupal transformation (stages of larval development), treatment and prevention measures are provided in this article.Results and discussion: This research has found that in the Chechen Republic the extensity of gadfly invasion was in the range 24,4% – 62,1%; the intensity of invasion was 9,8 – 24,0 larv./animal. Two gadfly species Hypoderma bovis De Geer and Hypoderma lineatum De Villers are causative agents of animal hypodermatosis. H. bovis is spread everywhere, H. lineatum - mainly in plain and piedmont of the republic. Gadfly flight in different natural-climatic zones of the republic is registered from the end of April until the middle of October.  Treatment and prevention measures continuously conducted for the whole livestock ( in spring against larvae of the 1st stage and in autumn - against larvae of the 2nd and 3rd development stages), taking into account ecological, phenological and epizootological situation in the region, may contribute to the full elimination of causative agents of hypodermatosis or their significant minimizing, reduction of economic damage to livestock of the republic.  Based on experimental data, the economically reasonable schedule of treatment and prevention measures has been created.